Mobile Agent Security Using Multilevel Secret Sharing with Changeable Threshold Based on Chinese Remainder Theorem - Asim, Mohammad; Sagar, Anil Kumar (Journal of Mobile Multimedia, 2025)
A novel computational technique known as mobile agent technology, just a little piece of code travels from one place to another. This code can migrate to another computer on the network that has agent functionality enabled and carry out the assigned task there. It is necessary to shield these agents from several risks and weaknesses both during their execution and travel in order to ensure their security. Based on the Chinese remainder theorem, the suggested approach involves multilevel secret sharing with a threshold that may be changed to secure mobile agents. One important aspect of this technique is that shareholders are arranged in a hierarchical or multilayer framework, with each owner requiring only one hidden private share because it will enable us to have smaller share sizes, making the process of transferring them easier and the complexity of recovery lower. This is a sample input file. Comparing it with the output it generates can show you how to produce a simple document of your own.